Post-apartheid racial integration in Grahamstown : a time-geographical perspective - Irvine, Philippa Margaret (Rhodes University, Faculty of Science, Department of Geography, 2012)
This research is situated within the context of the post-apartheid era in South Africa, which includes the dominant ideologies and policies that have shaped the urban landscape of the past and present. It investigates the extent and patterns of integration that exist twenty years after the country's political transition and it uses Grahamstown, a small education and cultural centre in the Eastern Cape Province, as its case study. The investigation incorporates the traditional geographical focus of residential and educational integration, using conventional means of investigation such as segregation indices, dissimilarity indices, percentages and maps. However, in identifying the broader nature of 'segregation' and 'integration', the study moves beyond these foci and approaches. It adopts the timegeographical framework to reveal the dynamic use of urban space that reflects the lived space of selected individuals from the community of Grahamstown: the extent and patterns of their behavioural integration or spatial linkages. Together, these approaches reveal that Grahamstown is still a city divided by race and, now, class. Schools and residential areas remain tied to the apartheid divisions of race and the white community exists almost entirely within the bounds of apartheid's blueprint of urban space. Rhodes University, which is located within Grahamstown, has experienced admirable levels of integration within the student body and within the staff as a whole, but not within the staff's different levels. In essence, where integration has occurred it has been unidirectional with the black community moving into the spaces and institutions formerly reserved for whites. The limited behavioural integration or spatial linkages are shown to be tied to city structure and, within the white group, to perceptions of 'otherness' held by the individuals interviewed. While the study shows limited differences in the time-spatial movements between members of different races who are resident in the former white group area, it highlights the differences between those more permanently resident in the city and the temporary educational migrants or students. The study argues that the slow pace of change is related to the nature of South Africa's democratic transition and its attending political and economic policies.
Keywords: Race discrimination -- South Africa -- Eastern Cape; Grahamstown (South Africa) -- Race relations; Grahamstown (South Africa) -- Social conditions